2012
DOI: 10.1371/journal.pone.0051967
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Promotes Acquisition of Stem Cell and Epithelial-to-Mesenchymal Properties in Head and Neck Squamous Cell Carcinoma

Abstract: The ability of nicotine to enhance the malignancy of cancer cells is known; however, the possibility that nicotine could regulate a cancer stem cell phenotype remains to be well-established. In this study we sought to determine whether long-term exposure to nicotine could promote cancer stem cell-like properties in two head and neck squamous cell carcinoma cell lines, UMSCC-10B and HN-1. Nicotine treatment induced epithelial-to-mesenchymal transition (EMT) in both cell lines by repressing E-cadherin expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…In mouse tumor transplantation models, nicotine increases the growth and metastasis of various tumor cells including the liver metastasis of orthotopically implanted pancreatic adenocarcinoma cells, subcutaneously injected head and neck squamous cell carcinoma cell lines and NNK-induced lung tumors (15)(16)(17). In particular, Wei et al showed that nicotine enhanced colon cancer cell migration through activation of α7 nicotinic acetylcholine receptor (nAChR) and induction of E-cadherin (12).…”
Section: Discussionmentioning
confidence: 99%
“…In mouse tumor transplantation models, nicotine increases the growth and metastasis of various tumor cells including the liver metastasis of orthotopically implanted pancreatic adenocarcinoma cells, subcutaneously injected head and neck squamous cell carcinoma cell lines and NNK-induced lung tumors (15)(16)(17). In particular, Wei et al showed that nicotine enhanced colon cancer cell migration through activation of α7 nicotinic acetylcholine receptor (nAChR) and induction of E-cadherin (12).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proposed that nicotine and nAChRs can contribute to stem-like functions of tumor initiating cells, by inducing embryonic stem cell transcription factors including Oct4 and Nanog (82, 83). Nicotine treatment also enhanced the expression of CD44 and BMI-1, and promoted the sphere formation capacity of squamous cell carcinoma cells (83).…”
Section: Additional Tumor-promoting Functions Of Nachrsmentioning
confidence: 99%
“…Nicotine treatment also enhanced the expression of CD44 and BMI-1, and promoted the sphere formation capacity of squamous cell carcinoma cells (83). Similar results have been reported in oral epithelial cells as well, supporting the contention that exposure to nicotine can promote EMT as well as stemness (82).…”
Section: Additional Tumor-promoting Functions Of Nachrsmentioning
confidence: 99%
“…miR‐29b was downregulated in response to alcohol (Qi et al, ) and stimulants (Eipper–Mains et al, 2011) and it was also reported to be upregulated in response to alcohol (Li et al, ), anesthetics (O'Connor et al, 2013), cannabinoids (Chandra et al, ) and opioids (Hu et al, ). Also, miR‐9 was upregulated in alcohol (Wang et al, ; Yadav et al, ; Balaraman et al, ), tobacco/nicotine (Yu et al, ) (Bala et al, ), opioids (Hu et al, ) and stimulants (Tatro et al, ; Varma and Kovtun, ) studies, and was downregulated in other alcohol studies (Balaraman et al, ; Balaraman et al, ; Sathyan et al, 2007; Qi et al, ). In addition, miR‐122 was downregulated in some alcohol studies (Bala et al, ; Li et al, ; Ignacio et al, ; Meng et al, 2012), while it was upregulated in other alcohol (Zhang et al, ; Bala et al, ; Dippold et al, ; Hou et al, ) and opioid (Qiu et al, ) studies.…”
Section: An Overview Of Distribution Of Mirna Studies On Da (Drugs Ofmentioning
confidence: 99%